Characterization of Zeolite ZSM-5 Synthesized from Kaolin and TPABr Using X-Ray Diffraction and Infrared Spectroscopy - Abdul Hamid; Faizatur Rohmah; Tri Esti Purbaningtias; Mohammad Abdullah (Universitas Islam Indonesia, 2023)
Kaolin with alumina and silica content is used as the main material in this research to study the synthesis of ZSM-5 zeolite. The hydrothermal process was carried out through different aging times, namely 12, 24 and 36 hours. Tetrapropyl ammonium bromide (TPABr) was used as a template for the Mobile Five-1 (MFI) structure guide. X-ray diffraction (XRD) and infrared spectroscopy (FTIR) instruments were used to characterize the ZSM-5 zeolite formed from the synthesis results. This was done to identify the phase change from kaolin to zeolite ZSM-5. The results of the analysis using XRD for all samples showed a characteristic peak of the ZSM-5 zeolite at 2θ around 7.88°; 8.72° ;23.09°; 23.84° and 24.32°. However, samples with an aging time of 12 hours also showed peaks at 2θ around 15.84° and 26.03° which indicated an analsim phase. The absorption bands from the FTIR characterization for all samples are seen at wave numbers around 453, 542, 793, 1088 and 1221 cm−1 which are the characteristic peak points of ZSM-5 zeolite. The longer the aging time indicates that the crystallinity of the ZSM-5 zeolite is increasing. The highest crystallinity was obtained from ZSM-5 zeolite samples which were aged for 36 hours. This indicates an increasing number of ZSM-5 crystal nuclei with high purity because there is no other phase besides the ZSM-5 phase.